Enhancing the Quality of Education in the Maldives : Challenges and Prospects - World Bank (Washington, DC, 2014)
The quality of education is a major policy challenge facing the Maldives. The country achieved the first generation objective of providing universal access to basic education through rapid expansion of enrollment. As is frequently the case with such countries, the second generation challenge is to provide education of adequate quality. Evidence from a variety of sources shows that education quality in the Maldives is weak, and needs urgent improvement. Learning outcomes in both primary and secondary education are modest. National assessments of learning outcomes at Grade 4 and Grade 7 show that learning levels are unsatisfactory. The low average scores suggest that learning levels in both primary education and lower secondary education are weak. There are several dimensions of education quality which Maldivian policy makers consider to be of vital importance. Among these, the quality of school teachers is central to the improvement of education quality. Hence, the Ministry of Education (MOE) is concerned to develop the skills, motivation and performance of teachers. A second key policy initiative is the establishment of a sound quality assurance framework for the school system. The MOE has developed a quality assurance mechanism, which now needs to be pilot tested, refined and scaled up throughout the country. A third strategic policy initiative is the development of a system of regular national assessments of learning outcomes, which can then feed into policy formulation and program development. These three strategic policy initiatives are discussed in the subsequent sections of this report.